The Difference Practice of Condom Usage to Direct and Indirect Woman Sex Worker in Preventing HIV at Sidoarjo - Sari, Elok Puspita; Hargono, Arief (Jurnal Berkala Epidemiologi, 2015)
ABSTRACTDirect Woman Sex Worker (Direct-WSW) is a woman who openly offers sex at street legal or illegal prostitution complexÂ  or ex legal or illegal prostitution complex, while Indirect Woman Sex Worker (Indirect-WSW) is a woman who operate in concealed as prostitute who works at certain job or has other main job and indirrectly offers sex at placesof entertainment as massager or public relation in bar or karaoke. The objective of this study is to know the difference practice using condom to direct-WSW and indirect-WSW in prevention against HIV in Sidoarjo. This study is an analytic observational study using survey method and case control approach. The population such as ndirect-WSW population is 20 people and direct-WSW population is 233 people. Determining the size for sample in hypothesis test using Lameshow formula by ratio 1:2 is gotten indirect-WSW sample for 20 people by total sampling technique and direct-WSW sample for 42 people by simple random sampling technique. The variables are characteristic and practice of both sample group. The result of the study shows that both respondent group are having high the practice of condom usage in preventing HIV in direct-WSW 73% and indirect-WSW 30%. The conclusion from this study is there is different practice in condom usage to direct-WSW and indirect-WSW in preventing HIV in Sidoarjo. The suggestion for further researchers to be able to expand the research sample, add other variable, and expand different research methodology like quantitative and experiment.Keywords: practice, Direct-WSW, Indirect-WSW, condom usage behavior, HIV prevention